Differential Regulation of c-di-GMP Metabolic Enzymes by Environmental Signals Modulates Biofilm Formation in Yersinia pestis - Ren, Gai-Xian; Fan, Sai; Guo, Xiao-Peng; Chen, Shiyun; Sun, Yi-Cheng (Frontiers in Microbiology, 2016)
Cyclic diguanylate (c-di-GMP) is essential for Yersinia pestis biofilm formation, which is important for flea-borne blockage-dependent plague transmission. Two diguanylate cyclases (DGCs), HmsT and HmsD and one phosphodiesterase (PDE), HmsP are responsible for the synthesis and degradation of c-di-GMP in Y. pestis. Here, we systematically analyzed the effect of various environmental signals on regulation of the biofilm phenotype, the c-di-GMP levels, and expression of HmsT, HmsD and HmsP in Y. pestis. Biofilm formation was higher in the presence of nonlethal high concentration of CaCl2, MgCl2, CuSO4, sucrose, sodium dodecyl sulfonate, or dithiothreitol, and was lower in the presence of FeCl2 or NaCl. In addition, we found that HmsD plays a major role in biofilm formation in acidic or redox environments. These environmental signals differentially regulated expression of HmsT, HmsP and HmsD, resulting in changes in the intracellular levels of c-di-GMP in Y. pestis. Our results suggest that bacteria can sense various environmental signals, and differentially regulates their DGCs and PDEs to coordinately regulate and adapt metabolism of c-di-GMP and biofilm formation to changing environments.